Unsteady mixed convection stagnation point flow over a plate moving along the direction of flow impingement using BVP4C / Norfarhana Idayu Mad Lela, Nur Iman Alia Lukman and Nurulhuda Ahmad Amir - Mad Lela, Norfarhana Idayu; Lukman, Nur Iman Alia; Ahmad Amir, Nurulhuda (2023)
The study focuses on unsteady mixed convection stagnation point flow over a plate moving along the direction of flow impingement. The purposes of this study are to apply similarity transformation to transform the nonlinear partial differential equation (PDE) into an ordinary differential equation (ODE) and to solve and analyse numerically the unsteady mixed convection stagnation point flow over a plate moving in the flow impingement direction by using the BVP4C method in the MATLAB software. The order of the PDE was chosen by the highest derivative. The methodology was divided into two phases, with the first focused on the examination of unsteady mixed convection flow and the second on numerical analysis utilizing the BVP4C method.